Epidermoid Cancer of the Anal Canal - Webb, Shawn P. (Thieme Medical Publishers, 2011)
Anal canal cancer is a rare cancer with incidence that continues to rise. This has been in large part due to increased prevalence of immunosuppressed conditions such as organ transplantation and human immunodeficiency virus along with transmission of the human papillomavirus. Identification of high-risk groups and close monitoring of these groups can help to detect earlier stages of cancer. Chemoradiation therapy remains the mainstay of treatment with excellent outcomes. Surgery for anal canal carcinoma remains as a salvage technique for failed chemoradiation or recurrent disease.